2002
DOI: 10.1124/mol.61.3.667
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the Cytoplasmic Interaction between Phospholamban and Ca2+-ATPase of Cardiac Sarcoplasmic Reticulum

Abstract: Phospholamban (PLN) reversibly inhibits the Ca2ϩ -ATPase of cardiac sarcoplasmic reticulum (SERCA2a) through a direct protein-protein interaction, playing a pivotal role in the regulation of intracellular Ca 2ϩ in heart muscle cells. The interaction between PLN and SERCA2a occurs at multiple sites within the cytoplasmic and membrane domains. Here, we have reconstituted the cytoplasmic protein-protein interaction using bacterially expressed fusion proteins of the cytoplasmic domain of PLN and the long cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…However, this strategy of purification and reconstitution followed by photoaffinity labeling (9) is difficult to execute with PLB and SERCA2a and has not been duplicated in other laboratories. More recent approaches to address physical interactions between PLB and SERCA2a are cryoelectron microscopy of PLB/SERCA2a co-crystals (20) and assessment of fusion protein interactions (21).…”
mentioning
confidence: 99%
“…However, this strategy of purification and reconstitution followed by photoaffinity labeling (9) is difficult to execute with PLB and SERCA2a and has not been duplicated in other laboratories. More recent approaches to address physical interactions between PLB and SERCA2a are cryoelectron microscopy of PLB/SERCA2a co-crystals (20) and assessment of fusion protein interactions (21).…”
mentioning
confidence: 99%
“…Conversely, mAb-A1 did not interfere with the binding of Apt-9 to PLN 1-26 -PDZ-Myc-His 6 at concentrations up to 50 g/ml (Fig. 3B), even though the antibody at this concentration almost completely inhibited the interaction between PLN 1-26 -PDZ-Myc-His 6 and the cytoplasmic domain of SERCA2a (Kimura and Inui, 2002) and maximally stimulated SERCA2a activity of cardiac SR vesicles (Kimura et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…To obtain DNA aptamers specific for the cytoplasmic region of phospholamban, we performed the SELEX protocol with an aptamer library based on a random 40-nucleotide sequence and with a fusion protein consisting of Met1-Gln26 of human phospholamban fused to the PDZ domains of PSD-95 followed by Myc epitope and His 6 tags (PLN 1-26 -PDZ-Myc-His 6 ), which retains the ability to interact with the cytoplasmic domain of SERCA2a (Kimura and Inui, 2002). PDZ-Myc-His 6 was used to remove aptamers that might bind nonspecifically to the fusion protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Removal of phospholamban-mediated inhibition of SERCA2a activity is thus a potential therapeutic option for treatment of heart failure and cardiomyopathy. 12,13 Chemical cross-linking of purified proteins suggests that phospholamban binds directly to SERCA2a. 14 Site-specific mutagenesis and transient expression of the mutant proteins in heterologous cells have revealed that 3 sites of interaction in the cytoplasmic domains and membrane helices of both phospholamban and SERCA2a contribute to the inhibitory effect of the former on the latter.…”
mentioning
confidence: 99%